2024
DOI: 10.1021/acscatal.3c04555
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Hydrodeoxygenation of Lignin Derivatives over Ni Single Atoms Supported on Mo2C

Haoquan Guo,
Jiwu Zhao,
Yu Chen
et al.

Abstract: Lignin derivatives are one class of attractive alternative feedstocks for the production of renewable biofuels. Herein, hydrodeoxygenation (HDO) of lignin derivatives was carried out using a single-atom catalyst (SAC) comprised of Ni 1 SAC on β-Mo 2 C. A number of lignin-derived compounds have been investigated, and nearly 100% yield of biofuel molecules was converted from various lignin derivatives through the HDO reaction, demonstrating that Ni 1 /β-Mo 2 C has remarkable potential for the production biofuels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…XANES spectra of the Ni K-edge of reduced LNO catalysts showed that the absorption edge is located between that of Ni foil and LaNiO 3 perovskite. As the reduction temperature increases, the edge position moved upward, indicating that Ni 3+ is gradually reduced to metallic Ni 0 (Figure a) . EXAFS of LaNiO 3 showed Ni–O (first coordination shell) with a bond distance of 1.44 Å and Ni–La (second coordination shell) with a bond distance of 2.41 Å (Figure b) .…”
Section: Resultsmentioning
confidence: 96%
“…XANES spectra of the Ni K-edge of reduced LNO catalysts showed that the absorption edge is located between that of Ni foil and LaNiO 3 perovskite. As the reduction temperature increases, the edge position moved upward, indicating that Ni 3+ is gradually reduced to metallic Ni 0 (Figure a) . EXAFS of LaNiO 3 showed Ni–O (first coordination shell) with a bond distance of 1.44 Å and Ni–La (second coordination shell) with a bond distance of 2.41 Å (Figure b) .…”
Section: Resultsmentioning
confidence: 96%